Development of a compact and sustainable CNC milling machine for PCB prototyping - Rosli, Hana Syahirah; Ayob, Mohammad Afif (2025)
The growing demand for printed circuit boards (PCBs) in various electronic applications calls for sustainable and accessible advancements in PCB manufacturing. Traditional fabrication methods are often manual, resource-intensive, and lack precision, making them unsuitable for rapid prototyping in educational or low-budget environments. This study presents a cost-effective desktop PCB milling machine prototype designed to support sustainable learning and innovation by enabling students and makers to produce high-quality PCBs in-house. The machine utilizes open-source Marlin firmware and is modeled using SolidWorks. It features mesh bed leveling, gantry movement, and real-time monitoring via the TFT43 V3.0 touchscreen integrated with the BigTreeTech SKR Mini E3 V3.0 control board, enhancing operational efficiency and user experience. Testing demonstrated the stepper motors high positional accuracy of 99.49% ± 0.1% on both X and Y axes, confirming the machine’s reliability for precise PCB layout production. This project promotes sustainable engineering education and provides a practical tool to advance digital fabrication and lifelong learning in the Industry 4.0 era.